Animal-derived ingredients in medicines: a framework for ethical prescribing practices - Lababidi, Hamdi; Bobier, Christopher; Rodger, Daniel (Frontiers in Pharmacology, 2025)
An increasing number of patients want to avoid animal-derived ingredients in medications due to ethical, religious, or cultural beliefs, yet transparency about these ingredients remains limited. Healthcare professionals often lack guidance on how to respect their preferences while ensuring effective treatment. Here, we propose an ethical pharmacotherapy modification framework that guides clinicians through a stepwise approach, altering manufacturer, dosage form, administration method, or medication itself, to accommodate patient values without compromising clinical efficacy. This framework balances respect for patient autonomy with clinical beneficence. Implementing this approach is likely to enhance patient trust and adherence by aligning pharmaceutical care with individual ethical considerations and promoting patient-centered care.